Determination of Collective Premiums for Seven Benefits of BPJS Employment Insurance JKK Program Using Poisson-Normal Aggregate Distribution - Maghfirani, Nazla Aqira; Hidayana, Rizki Apriva (Research Collaboration Community (RCC), 2025)
Work Accident Insurance (JKK) is one of the programs of the Social Security Administering Agency (BPJS) for Employment. Insurance brokers need to make an initial estimate of the premium to determine the collective premium for JKK. Premium calculations can be done using the aggregate distribution method. The total loss of the insurance policy can be owned by the random variable of the aggregate distribution. In calculating the premium using the aggregate distribution, one of the principles that can be used is the standard deviation principle. Based on this principle, the amount of the premium can be calculated by the standard deviation of the aggregate distribution. This study uses the aggregate Poisson-Normal distribution to calculate the collective premium based on the seven benefits of the JKK BPJS Ketenagakerjaan Bojongsoang program. The data used are the number of claim events and the number of claims from the seven benefit claims of JKK BPJS Ketenagakerjaan Bojongsoang participants for the 2022 period. The principle used in calculating the collective premium with the aggregate distribution is the standard deviation principle. The results of the analysis show that the Poisson distribution is followed by claim frequency data and the Normal distribution is followed by the amount of the claim. This study shows that the amount of collective premium calculated tends to be greater than the amount of collective premium sourced from existing data of BPJS Ketenagakerjaan Bojongsoang company. It is expected for insurance brokers and insurance companies to consider this study.